Insertion/Deletion Polymorphisms and Serum Angiotensin-converting Enzyme Levels in Iranian Patients with Sarcoidosis - Alireza JAVADI; Masoud SHAMAEI; Masoud ZAREI; Lida REZAEIAN; Arda KIANI; Atefeh ABEDINI (Tehran University of Medical Sciences, 2016)
Background: Sarcoidosis is a multisystem inflammatory disease of unknown origin with characterization of small granulomas. Angiotensin-converting enzyme (ACE) is a pathophysiologic marker of sarcoidosis. We present the ACE insertion/deletion (I/D) polymorphism in correlation with serum ACE level in Iranian patients with sarcoidosis. Methods: From Jan 2014 to Jan 2015, 102 Iranian patients who histopathologically diagnosed for sarcoidosis and 192 healthy age and sex-matched controls were recruited. PCR was used for detection of I/D polymorphism in ACE gene. Results: Frequency of II/ID/DD genotype in sarcoidosis disease was 17%, 35.5%, and 47.1%, respectively. The frequency of D allele was 0.65. A significant association between I/D genotypes and mean of sACE level was seen (DD=85.2±22.9, P<0.001). More frequent genotype in sarcoidosis patients was DD (47%), ID genotype (45.9%) was found more in controls. Logistic regression analysis adjusting age and sex showed that ID to II (OR=0.35, 95%CI=0.17-0.73, P=0.005) and DD to II (OR=2.11, 95%CI=0.98-4.54, P=0.05) could be considered as a predictor factor for the disease activity. No significant model for men in sarcoidosis group was seen, while women with II/ID were associated with a reduced risk for the disease. Conclusion: Although more regional studies with appropriate statistical scale must be done to provide a better diagnosis and prognostic tool for this disease, this study demonstrates that ID and DD genotype could be predictive factors for sarcoidosis.   Keywords: Sarcoidosis, ACE gene polymorphism, Angiotensin converting enzyme